Case report: A novel STXBP1 splice variant and the landscape of splicing-involved STXBP1-related disorders - Wang, Haiping; Chen, Xiuli; Liu, Zhanli; Chen, Chen; Liu, Xin; Huang, Mingwei; Zhou, Zhuying (Frontiers in Neurology, 2023)
STXBP1 variants are one of the most common genetic causes of neurodevelopmental disorders and epilepsy, wherein STXBP1-related disorders are characterized by neurodevelopmental abnormalities in 95% and seizures in 89% of affected patients. However, the spectrums of both genotype and phenotype are quite wide and diverse, with a high baseline variability even for recurrent STXBP1 variants. Until now, no clear genotype–phenotype correlations have been established and multiple disease mechanisms have been proposed for STXBP1-related disorders. Without an ascertained disease cause for many cases of STXBP1 variants, it is challenging to manage this disease in an effective manner and current symptom-based treatments are focused on seizure control only, which has a minimal impact on global development. A novel STXBP1 canonical splice variant, NM_001032221.4:c.578+2T>C, was reported in this study, together with detailed documentation of disease manifestations and treatment management. Further RNA expression analysis revealed abnormal intron retention and possible production of truncated STXBP1 proteins as a likely pathogenic mechanism. More importantly, the landscape of previously understudied STXBP1 splice variants and functional investigations was assessed for the first time to provide a context for the discussion of the complicated genotype–phenotype relationship of STXBP1-related disorders. Future cases of this disorder and a deeper mechanism-based understanding of its pathogenic cause are required for precision medicine and better disease management.